2013
DOI: 10.1155/2013/345479
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Fibromyxoma of Maxilla: A Rare Case Report

Abstract: Fibromyxoma is a rare odontogenic tumour which is benign, but locally aggressive. The etiology of these tumours is unknown, but because of its limitation to the teeth bearing areas and occasional presence of odontogenic epithelial fragments within the tumour which suggest that it is of odontogenic origin. It is a slow growing painless tumour that frequently occurs in second and third decades of life. Females are more commonly affected than males. The tumour can cause gradual expansion of the cortical plates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 10 publications
1
34
0
4
Order By: Relevance
“…Fibromyxomas express vimentin and are typically negative for S-100, CD34, SMA, and CD68 [19]. A summary of the reported demographics and histopathological characteristics of odontogenic fibromyxomas published within the last 10 years is provided in Table 1 [14,18,[20][21][22][23][24][25][26].…”
Section: Gross and Histopathologic Characteristics Of Fibromyxomamentioning
confidence: 99%
“…Fibromyxomas express vimentin and are typically negative for S-100, CD34, SMA, and CD68 [19]. A summary of the reported demographics and histopathological characteristics of odontogenic fibromyxomas published within the last 10 years is provided in Table 1 [14,18,[20][21][22][23][24][25][26].…”
Section: Gross and Histopathologic Characteristics Of Fibromyxomamentioning
confidence: 99%
“…It accounts for only 1 to 3% of all tumors of the jaws, with an incidence rate of 0.07% new cases per million people per year. 6 Myxomas of jaws may be odontogenic in origin (HmTison, 1973). As bony myxomas almost exclusively occur only in the jaws, it is also suggested that they arise from the mesenchyme of the tooth germ (Pindborg, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…This involves enucleation and curettage, radical surgery and en block resection depending on the size of tumor. 8,6 There have been higher recurrence rate for this tumor between 25% and 43%. 8 This recurrence is mostly due to incomplete removal of tumor rather than true recurrence.…”
mentioning
confidence: 89%